The distribution of microplankton in the McMurdo Dry valley lakes, Antarctica: response to ecosystem legacy or present-day climatic controls - Roberts, EC; Priscu, JC; Wolf, C; Lyons, WB; Laybourn-Parry, J (2004)
Plankton abundance and biomass were investigated in five lakes of the McMurdo Dry Valleys, Antarctica: Lakes Bonney, Fryxell, Joyce, Hoare and Miers. Despite plankton communities being dominated by organisms <100 Î¼n in length, there were striking differences between the lakes, including large variations in plankton vertical distribution and differences in total plankton biomass. Bacterial biomass was highest in the anoxic monimolimnia of the meromictic lakes, reaching 191 Î¼g C l-1 in Lake Fryxell. Photosynthetic nanoflagellates dominated phytoplankton in the five lakes studied. Highest chlorophyll a concentrations were recorded at the chemocline of Lake Fryxell (21 Î¼g chl a l-1). Heterotrophic nanoflagellate concentrations were low, ranging from 2 cells ml-1 in Hoare to 237 cells ml-1 in Bonney. By Antarctic standards, cillates were relatively successful in terms of biomass and diversity in Lakes Fryxell and Hoare. In contrast, Lake Miers possessed extremely low ciliate abundance (<0.04 cells ml-1). On both sampling occasions, copepod nauplii were observed in Lake Joyce. This is the first recording of crustacean zooplankton within the McMurdo Dry Valley Lakes. Because the foodwebs of these lakes are structured by "bottom-up" forces, differences in plankton distributions could be related to the physicochemical characteristics of each lake. The effect of lake evolution (legacy) and present-day climate change on planktonic dynamics is discussed. Â© Springer-Verlag 2003.